Synthesis and Characterization of Hydrogel from Sago Pith Waste Derived Cellulose for Agricultural Application - Angeline Lecca, anak Wilbert Jampi (Universiti Malaysia Sarawak (UNIMAS), 2022)
The large amount of sago pith waste (SPW) produced by the growing sago industry has become an environmental concern. Instead of being disposed of, SPW could be converted to hydrogel and used for water hydration. In this study, the hydrogel was prepared from SPW cellulose fibers via crosslinking with epichlorohydrin (ECH). FTIR characterization showed that pure cellulose fibers extracted from the SPW were successfully crosslinked with ECH to form the hydrogel. SEM micrograph of hydrogel showed porous microstructure. The optimum swelling ratio of the hydrogel at 19.9 g.g−1 was obtained with 5% SPW cellulose content and 5 mL ECH. In this study, the hydration property of the hydrogel was demonstrated by using it as a medium for maize seed germination. The germination rate (GR) was above 70% when tested in SPW cellulose hydrogel as the medium for the treatment which consisted of 5 g of water and 0.05g of dried hydrogel had shown GR exceeded the control to 100%. The ammonium nitrate release profile of the SPW cellulose hydrogel has demonstrated the intensive release for the first 10 minutes and wavered until the end of the experiment time. Overall, it is concluded that cellulose obtained from local SPW can be synthesized into hydrogel which can be used as growing medium for germinating seeds.